Identify Student’s Scientific Reasoning Skill in Straight Motion Material - Devian Astika Wati; Wahono Widodo; Sifak Indana (Indonesia Emerging Literacy Education, 2023)
Objective: This study aims to identify the level of scientific reasoning skills of students. Method: The type of research used is descriptive quantitative. The subjects of this study were 10th-grade students at 1st State SHS Menganti. The test given is five questions, each of which includes four indicators of scientific reasoning skills: theoretical reasoning, correlational reasoning, proportional reasoning, and probabilistic reasoning. The research method used is a preliminary study through reviews, determining research objectives, developing research instruments, validating instruments, collecting data, and analyzing and interpreting data. Results: The results of the research conducted show that the level of students' scientific reasoning skills in the theoretical reasoning pattern is quite good because they can interpret the existing theory with the data on the problem. Students' scientific reasoning skills in the correlational reasoning pattern still need to improve because only one student can answer questions at level 5. Students' scientific reasoning skills in the proportional reasoning pattern still need to improve because only one student's answer reaches the level 4 Ratio (R). The students' scientific reasoning skills in the probabilistic reasoning pattern still need to improve because only three are at level 3. Novelty: With this research, it is hoped to provide information about the importance of training students' scientific reasoning skills. Scientific reasoning skills are essential and related to science education (not only in scientific contexts but also in everyday life).